2019
DOI: 10.1097/mlr.0000000000001223
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of Nursing Homes and Long-term Residents in Medicare ACOs

Abstract: Background: Long-term nursing home residents have complex needs that often require services from acute care settings. The accountable care organization (ACO) model provides an opportunity to improve care by creating payment incentives for more coordinated, higher quality care. Objectives: To assess the extent of nursing home participation in ACOs, and the characteristics of residents and their nursing homes connected to ACOs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Although the mechanisms are unclear, our results provide evidence of risk selection on dementia status resulting in substantially lower enrollment of such patients in ACOs, including dementia patients dwelling in the community. Prior studies focused solely on nursing home patients with dementia and also found lower ACO enrollment 23–26 . These results confirm prior predictions that ACOs would be incented to engage in risk selection to avoid patients with dementia due to a lack of risk adjustment for this condition by Medicare 22 .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Although the mechanisms are unclear, our results provide evidence of risk selection on dementia status resulting in substantially lower enrollment of such patients in ACOs, including dementia patients dwelling in the community. Prior studies focused solely on nursing home patients with dementia and also found lower ACO enrollment 23–26 . These results confirm prior predictions that ACOs would be incented to engage in risk selection to avoid patients with dementia due to a lack of risk adjustment for this condition by Medicare 22 .…”
Section: Discussionsupporting
confidence: 77%
“…Prior studies focused solely on nursing home patients with dementia and also found lower ACO enrollment. [23][24][25][26] These results confirm prior predictions that ACOs would be incented to engage in risk selection to avoid patients with dementia due to a lack of risk adjustment for this condition by Medicare. 22 Such patterns had been seen previously in the MA program, 41 where dementia was also not included in the risk models that determined per-member payment rates.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…When collaborating entities in an ACO succeed in delivering high-quality care at a lower cost, the group shares in the savings it realizes. 31 …”
Section: Literature Reviewmentioning
confidence: 99%
“…A complex mix of for‐profit, private, and public ownership usually means that LTSS facilities and nearby hospitals are not part of the same vertically integrated system. Memoranda of understanding (MOUs) or formal contracts reflecting the now popular models of “patient‐centered medical homes” or “accountable care organizations” may be a philosophical as well as a practical answer to such gaps in coordination 75 …”
Section: Recommendationsmentioning
confidence: 99%